(untitled) (Historia, 2021)
A favourite denouement of fiction, and one which never fails to please, is the last-minute reprieve. In actuality an eleventh hour salvation is less common and, on that account, the more impressive. The nick-of- time saving by the Historical Monuments Commission of the homestead of General Andries Pretorius at Edendale, near Pietermaritzburg, is a particular case in point. The story, however, is best told from the beginning! In the 1930s the then Archivist of the Natal Archives Depot, Martin Basson, assembled verbal evidence from persons of all race groups of the Edendale vicinity to the effect that the building then known as the "school-room" was the original homestead of the Voortrekker hero, Andries Pretorius. Lack of positive documentary proof and discrepancies in the evidence moved the Historical ,7Jfonuments Commission, however, to reject the pro. position, subsequent developments entirely supporting this rejection. For reasons unknown the matter was then laid to rest for almost three decades.